Ginkgetin from Ginkgo biloba: mechanistic insights into anticancer efficacy - Bei Xiong; Jin-Jian Lu; Hongwei Guo; Mingqing Huang; Ting Li (Natural Products and Bioprospecting)
Abstract The extraction of anticancer agents from medicinal plants represents a highly promising research frontier. Ginkgetin, a natural biflavone, is one of the effective pharmacological components of Ginkgo biloba leaves (GBLs). This natural product exhibits significant anti-cancer efficacy against a variety of cancer cells in vitro and demonstrates a potent inhibitory impact on tumor growth in vivo without severe toxicity. Additionally, ginkgetin synergizes with chemotherapy drugs or adjuvant therapies to potentiate antitumor effects and reduce side effects. These compelling findings underscore Ginkgetin's potential as a promising candidate for novel anti-cancer therapeutics. Therefore, this review systematically summarizes the remarkable anticancer effects of ginkgetin and elucidates its multifaceted anticancer mechanisms, including inducing cell cycle arrest, triggering programmed cell death, and preventing invasion and angiogenesis. From a molecular mechanism perspective, ginkgetin exerts anti-cancer activity by modulating critical signaling pathways (e.g. JAK/STAT, Wnt/β-catenin, AKT/GSK-3β, MAPKs, and estrogen receptor pathways) and regulating microRNA expression levels. Furthermore, target identification, research limitations, future directions, and application prospects are comprehensively outlined, aiming to facilitate the clinical translation of ginkgetin. Graphical Abstract